If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5.6 + -0.8y + -1y = -2 Combine like terms: -0.8y + -1y = -1.8y -5.6 + -1.8y = -2 Solving -5.6 + -1.8y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5.6' to each side of the equation. -5.6 + 5.6 + -1.8y = -2 + 5.6 Combine like terms: -5.6 + 5.6 = 0.0 0.0 + -1.8y = -2 + 5.6 -1.8y = -2 + 5.6 Combine like terms: -2 + 5.6 = 3.6 -1.8y = 3.6 Divide each side by '-1.8'. y = -2 Simplifying y = -2
| x+6+x+3+x+9+x+1+x+1+x+4+x+4= | | 0.5x-3=0.3(2x-3) | | -4.7k=10.81 | | x(13)=104 | | x(5)=55 | | 7t-2(-3t+1)=-3(1-3t) | | 8m-10=62+2m | | -11x+9=185 | | x+2(2)=0 | | 6d+5=-4-3d | | X+(x-355)+(2x+80)=2425 | | 3(-2y)+y=-10 | | 18-x=1 | | y=-16-16 | | -2(3y+4)=20 | | -1/3+1= | | 8y-2y+13=2y+12 | | 5w^2-6w+17=8 | | 6x^3-77x^2+56x+8=0 | | 48y-4(6-y)=12(3y+2) | | -3x-14=1 | | fu=3 | | -7(x+8)=35 | | 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= | | 6(x+4)=3(4-2) |